Kajian Linguistik terhadap Campur Kode dalam Lirik Lagu Garam dan Madu Karya Tenxi, Jemsii, dan Naykilla - Anggun Citra Dini Dwi Puspitasari; Rahmawati Rahmawati (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
The lyrics of the song “Garam dan Madu” by Tenxi, Jemsii, and Naykilla present a unique multilingual phenomenon by combining Indonesian, Javanese, and English within a single lyrical composition, making them highly relevant for sociolinguistic analysis. This study aims to identify and analyze the types of code-mixing used in the lyrics through a descriptive qualitative method, employing interpretation, classification, and data decomposition techniques. The results show that the song incorporates both inner code-mixing, reflected in the use of Javanese within Indonesian structures, and outer code-mixing, marked by the presence of English lexical elements. Additionally, the lyrics exhibit various forms of code-mixing, including insertion, alternation, and congruent lexicalization, each contributing to the song’s stylistic variation and expressive depth. Overall, the findings illustrate how multilingualism in contemporary Indonesian music functions as a creative tool for identity expression, cultural blending, and emotional nuance, highlighting the increasingly hybrid linguistic practices found in youth-centered musical works.